A FRIEND for assisting handicapped people. - Martens, C.
The semiautonomous robotic system ?FRIEND? consists of an electric wheelchair with the robot arm MANUS. Both devices are controlled by a computer. The user interface consists of a flat screen and a speech interface. The system is for use by persons with upper limb impairments as well as disability of the legs. FRIEND's hardware and software are described. The current state of development is then presented, as well as research results that will be integrated soon. After an explanation of the speech interface, the methods developed for semiautonomous control are described. These are programming by demonstration, visual servoing, and configuration planning based on the method of imaginary links
Keywords: FRIEND; Configuration planning; Demonstration based programming; Electric wheelchair; Flat screen; Handicapped persons; Imaginary links; Robot arm MANUS; Semiautonomous control; Semiautonomous robotic system; Speech interface; Upper limb impairments; User interface; Visual serving